HCV Genotype-3h, a Difficult-to-Diagnose Sub-Genotype in the DAA Era. Issue 7 (October 2018) - Minichini, Carmine; Starace, Mario; De Pascalis, Stefania; Macera, Margherita; Occhiello, Laura; Caroprese, Mara; Vitrone, Martina; Iovinella, Vincenzo; Guerrera, Barbara; Masarone, Mario; Coppola, Nicola
Background: No data are available on the clinical presentation and virological pattern in the case of failure of interferon (IFN)-free regimens in patients with genotype-3h. In this paper authors identified the virological and clinical characteristics of patients with genotype-3h treated with suboptimal or not indicated IFN-free regimens for the misclassification of HCV genotype. Methods: A total of 87 consecutive patients with failure to an IFN-free regimen were re-tested for HCV genotype by HCV NS5B sequencing; the 26 patients identified as harbouring HCV-3 were enrolled. Results: Of the 26 patients enrolled, 4 (15.4%) harboured sub-genotype-3h and 22 (84.6%) 3a. All patients were Italian. Patients with genotype-3a infection were younger (median age 56 years, range 47–78) compared to those with genotype-3h infection (median 74 years, range 65–79; P <0.006). With regard to the failed direct-acting antiviral (DAA)-regimens, three of the four patients with genotype-3h (75%) had been treated with an ineffective DAA regimen (paritaprevir, ombitasvir, dasabuvir ± ribavirin for 3 months) more frequently than those with genotype-3a (13.6%; P =0.02), because of previous erroneous identification of HCV-1 genotype. NS5A resistance-associated substitutions (RASs) were observed in 10 (45.4%) genotype-3a-infected patients and in 2 (50%) with genotype-3h. NS5B RASs were observed in only two genotype-3a-infected patients and in none of the 3h-infected patients. Conclusions: This is the first time genotype-3h has been identified in Italian patients failing an IFN-free regimen, in the majority of cases because of a misclassification of the HCV genotype.